The Way of the Buddha - India. Ministry of Information and Broadcasting. Publications Division (New Delhi : Publications Division, Ministry of Information and Broadcasting, Govt. of India, 1995)
On Buddhist art and antiquity.
Companion volume to 2500 years of Buddhism.
Includes bibliographical references (p. [329]-[330]).
Includes passages in Pali and Sanskrit.
Keywords: Buddhist sculpture; Buddhist gods, in art